2013
DOI: 10.1002/ggge.20245
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for weak ferromagnetic moment within the basal plane of hematite natural crystals at low temperature

Abstract: [1] Low-temperature magnetization of hematite within the basal plane has been studied in a collection of natural crystals by means of torque magnetometry. Comparison between the torque curves at room temperature and at 77 K allows identification of a weak ferromagnetic moment constrained within the basal plane at temperatures well below the Morin transition. Annealing the samples produces the expected reduction of the weak ferromagnetic moment, but there is also a relationship between the ferromagnetic moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…4–5, Figure ] show that only part of the low‐temperature moment can be annealed out; annealing apparently reduces the number of strain centers but does not remove all of them. Similar results are reported by Martín‐Hernández and Hirt [].…”
Section: Room Temperature Hysteresis Resultssupporting
confidence: 91%
“…4–5, Figure ] show that only part of the low‐temperature moment can be annealed out; annealing apparently reduces the number of strain centers but does not remove all of them. Similar results are reported by Martín‐Hernández and Hirt [].…”
Section: Room Temperature Hysteresis Resultssupporting
confidence: 91%
“…There is substantial literature on the magnetic properties [1, 13,14] and Mössbauer [13,15] spectra of natural and synthetic hematite nanoparticles. It is generally found that the Morin transition moves to lower temperature with reduced particle size and that it is sharply reduced in particles smaller than about 100 nm [13].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of magnetism in hematite was explained by Zubov et al [5] based on the investigation of natural faces of the hematite band calculating the energy of surface anisotropy for the faces of types (100) and (111). Weak ferromagnetic moment within the basal plane of hematite natural crystals at low temperatures was explained by Hernandez [6].…”
Section: Introductionmentioning
confidence: 95%